Crosslinking of transcription factor TFIIIA to ribosomal 5S RNA from X. laevis by trans-diamminedichloroplatinum (II). - Baudin, F (1989)
Trans-diamminnedichloroplatinum (II) was used to induce reversible crosslinks between 5S rRNA and TFIIIA within the 7S RNP particle from X. laevis immature oocyte. The crosslinked fragments have been unambiguously identified. These fragments exclusively arise from three RNA regions centered around the hinge region at the junction of the three helical domains. Major crosslinking sites are located in region 9-21 (comprising loops A and helix II) and region 54-71 (comprising loop B, helices II and V). A minor site is also found in the 3' part of helix I and helix V (region 100-120). Our results point to the crucial role of the junction region and of the three-dimensional folding of the RNA in the recognition of the 5S rRNA by TFIIIA.